SIGNR1-mediated phagocytosis, but not SIGNR1-mediated endocytosis or cell adhesion, suppresses LPS-induced secretion of IL-6 from murine macrophages. Issue 1 (January 2015) - Kawauchi, Yoko; Takagi, Hideaki; Hanafusa, Kei; Kono, Mirei; Yamatani, Minami; Kojima, Naoya
Highlights LPS-induced secretion of IL-6 but not TNF-α is suppressed by SIGNR1-mediated phagocytosis. LPS-induced IL-6 secretion is not suppressed by SIGNR1-mediated endocytosis or cell adhesion. Phagocytosis do not interfere with IL-6 mRNA transcription, but affects IL-6 mRNA stability. A PI3 kinase inhibitor blocks the suppression of IL-6 secretion by SIGNR1-mediated phagocytosis.